2012
DOI: 10.5582/irdr.2012.v1.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis and liver transplantation

Abstract: Primary biliary cirrhosis (PBC) is an immune-mediated chronic progressive inflammatory liver disease, predominantly affecting middle-aged women, characterized by the presence of antimitochondrial antibodies (AMAs), which can lead to liver failure. Genetic contributions, environmental factors including chemical and infectious xenobiotics, autoimmunity and loss of tolerance have been aggressively investigated in the pathogenesis of PBC, however, the actual impact of these factors is still controversial. Survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 211 publications
(261 reference statements)
0
14
0
4
Order By: Relevance
“…Evidence has shown that surgical resection and liver transplantation may offer the best opportunity for treating HCC yet are only available to early-detected patients (13)(14)(15)(16). The normal overall 5-year survival rate is 40%, but with a liver resection to treat early HCC, the 5-year survival rate rise to 60-70% (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that surgical resection and liver transplantation may offer the best opportunity for treating HCC yet are only available to early-detected patients (13)(14)(15)(16). The normal overall 5-year survival rate is 40%, but with a liver resection to treat early HCC, the 5-year survival rate rise to 60-70% (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed performed liver transplantaion for PBC is uncertain (Akamatsu & Sugawara 2012) , whether patients can benefit from protocal biopsies needs further study. Previous studies have identified several factors associated with rPBC, including age, number of HLA mismatches, and the use of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 6,000 liver transplants have been performed in the United States and Europe for PBC [31]. The number of liver transplants for PBC has decreased over the past two decades [17].…”
Section: Risk Score Uk-pbcmentioning
confidence: 99%